2022
DOI: 10.1038/s41598-022-06389-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of preoperative sagittal spinal imbalance on pain after lateral lumbar interbody fusion

Abstract: Sagittal misalignment has been associated with negative quality of life (QOL). However, there is no report on whether differences in preoperative sagittal misalignment in patients with lumbar degenerative diseases affect postoperative results after lateral lumbar interbody fusion (LLIF). We investigated whether preoperative sagittal alignment influences the correction of alignment after surgery and whether the preoperative sagittal alignment affects the rating of low back pain, leg pain, and leg numbness. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…However, the mean length of stay in our study was around 20 days, which likely improved the accuracy of the outcome evaluation. Although this mean length of stay is much longer than in Western countries,21,50 it is consistent with other work from Japan 29,51. In addition, a sensitivity analysis, in which we extended the term of SSI from 30 to 90 days after surgery showed consistent results.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, the mean length of stay in our study was around 20 days, which likely improved the accuracy of the outcome evaluation. Although this mean length of stay is much longer than in Western countries,21,50 it is consistent with other work from Japan 29,51. In addition, a sensitivity analysis, in which we extended the term of SSI from 30 to 90 days after surgery showed consistent results.…”
Section: Discussionsupporting
confidence: 89%
“…Although this mean length of stay is much longer than in Western countries, 21,50 it is consistent with other work from Japan. 29,51 In addition, a sensitivity analysis, in which we extended the term of SSI from 30 to 90 days after surgery showed consistent results. Thus, we do not consider that this limitation should overturn our findings.…”
Section: Discussionmentioning
confidence: 64%
“…Various reports have been published on postoperative pain. 16 , 17 , 18 At present, factors affecting patients' postoperative pain can be broadly grouped into categories of sex, 19 obesity, 20 preoperative opioid abuse, 21 preoperative chronic pain, 22 and many other factors. Molecular analysis of the factors involved in post‐spine surgery pain may lead to new treatment methods.…”
Section: Discussionmentioning
confidence: 99%
“…After restoring the height of the intervertebral space, the volume of the intervertebral foramen increased by 39.6%, resolving the leg numbness caused by nerve root compression [ 23 ]. In addition, spinal sagittal imbalance caused by degenerative scoliosis also caused leg numbness and PI-LL was found to be significantly positively correlated with SVA ( r = 0.647, P < 0.001) [ 24 ]. The study of Aoki et al also found that PI-LL was significantly correlated with the occurrence of leg numbness after spinal endoscopy, which indicated that PI-LL mismatch would affect the symptoms of leg numbness after surgery [ 25 ].…”
Section: Discussionmentioning
confidence: 99%